Determinan Resiliensi Keluarga pada Orang Tua: Trait dan Positivity - Tessalonika Sembiring; O. Irene Prameswari Edwina (Universitas Kristen Maranatha, 2024)
The aim of this study is to determine the role of traits in family resilience, with positivity as a mediator. Data were collected using The Big Five Inventory (BFI), The positivity questionnaire and the family resilience questionnaire. The data were analyzed using the Hayes PROCESS model 4. Research respondent consisting of 272 parents (mostly female and average age of 44 years). The results of the study showed that positivity (positive and negative emotions) acts as a mediator between the five types of traits (neuroticism, extraversion, openness, agreeableness, and conscientiousness) toward family resilience. Traits will have a greater role on family resilience if mediated by positive emotions and negative emotions. However, positive emotions have a greater impact than negative emotions as mediators between traits and family resilience. However, the impact of positive emotions was stronger than the impact of negative emotions on family resilience. In future research, it is recommended that attention be paid to the degree of stress experienced by respondents, which may be an important variable in describing the adversity faced by parents.